2013
DOI: 10.1155/2013/782861
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Molecular Effects of Angiotensin II and Angiotensin III in Rat Astrocytes

Abstract: It is postulated that central effects of angiotensin (Ang) II may be indirect due to rapid conversion to Ang III by aminopeptidase A (APA). Previously, we showed that Ang II and Ang III induced mitogen-activated protein (MAP) kinases ERK1/2 and stress-activated protein kinase/Jun-terminal kinases (SAPK/JNK) phosphorylation in cultured rat astrocytes. Most importantly, both peptides were equipotent in causing phosphorylation of these MAP kinases. In these studies, we used brainstem and cerebellum astrocytes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our lab has previously reported the presence of functional astroglial AT1Rs in the brainstem and cerebellum of normotensive rats (Clark et al . , ; Kandalam and Clark ). Ang II via the AT1R can activate several signaling pathways that are critical to astrocyte functions such as regulation of inflammation (Kandalam and Clark ) and proliferation (Clark et al .…”
mentioning
confidence: 97%
“…Our lab has previously reported the presence of functional astroglial AT1Rs in the brainstem and cerebellum of normotensive rats (Clark et al . , ; Kandalam and Clark ). Ang II via the AT1R can activate several signaling pathways that are critical to astrocyte functions such as regulation of inflammation (Kandalam and Clark ) and proliferation (Clark et al .…”
mentioning
confidence: 97%
“…In previous studies, we have established the roles of Ang III in cultured astrocytes isolated from neonatal rat pups. We demonstrated that Ang III, similarly to Ang II, stimulated mitogen activated protein kinases (MAPKs) as well as the JAK2/STAT3 signaling pathways, leading to astrocyte proliferation [8,12,20,21,22,23]. Additionally, Ang III increased IL-6 secretion and the expression of IL-6 mRNA through activation of the JAK2/STAT3 cascade, suggesting pro-inflammatory effects of the peptide [8].…”
Section: Discussionmentioning
confidence: 99%
“…Three hundred nano mole per liter insulin was added 5 min prior to assay start. To protect AngII from cleavage, incubations were conducted in the presence of the aminopeptidase A inhibitor, amastatin (Sigma-Aldrich, Poland) at a concentration of 10 μmol/L ( 26 , 27 ). Thirty min before the start of measurement, media was replaced by reaction media (RM) containing RPMI 1640 supplemented with 0.5, 1.0, 5.6, or 30 mmol/L glucose.…”
Section: Methodsmentioning
confidence: 99%